An Empirical Study on Vietnamese Chocolate Consumers’ Behaviors and Purchasing Paradigms: A New Approach with Innovation Resistance Theory (IRT) for Downstream Chocolate Businesses in Vietnam - Tran, Van Lieng (Digital Repository of Theses, 2025)
This study applies Innovation Resistance Theory (IRT) to analyze consumer resistance in context, using domestically produced chocolate consumption in Vietnam as a case. The primary objective is to analyze how resistance to innovation in terms of usage, and risk barriers, as well as psychological ones such as image, affects consumers' purchasing intentions towards domestically produced chocolate products. The analysis also considers cultural values like collectivism, as well as consumer traits like innovative individuals, openness to change, in moderating resistance barrier development in a purchasing context. A quantitative approach was used to collect data through offline and online surveys to ensure diversity and representative sampling. The data were collected from 415 Vietnamese consumers between January and March 2025, and all of them had been exposed to and were aware of domestic chocolate brands. After collecting the survey, we did the data screening in SPSS by eliminating inconsistent, outlier, and incomplete data. The final dataset was then analyzed using SmartPLS, a capable statistical software for testing complex conceptual frameworks consisting of multiple latent variables, through SEM techniques. The results show that the risk barrier, one of the resistance barrier types, has a significant and negative relationship with consumers’ purchase intention. In other words, customers are not willing to buy domestic chocolate the more they perceive it as risky, for example, in terms of quality, safety, or the uncertainty of origin. Besides, usage barrier and image barrier are identified, but their results are substratified by socio-cultural and psychological characteristics. Specifically, consumers who score high on collectivism are more likely to be affected by image barriers, presumably because social norms and group-oriented decision-making processes play a fundamental role in their consumption decisions. On the other hand, consumers scoring high on changeability and innovativeness tend to be less affected by resistance barriers overall. Based on these results, the study suggests that producers, marketers, and retailers of domestic chocolate products in Vietnam should design targeted strategies to overcome innovation resistance. Marketing campaigns can emphasize product safety, quality assurance, and positive brand image to reduce perceived risk and image barriers. At the same time, it is important to align messaging with cultural values like collectivism, which may involve community endorsements, social proof, or group-based incentives. Finally, initiatives that foster innovation-friendly mindsets through product sampling, storytelling, or interactive campaigns could prove effective in enhancing acceptance and adoption of locally made chocolate. Keywords: Innovation Resistance Theory (IRT), purchase intention, domestic chocolate products, consumer behavior, Vietnam